CONSERVATION PRACTICES AND RESTORATION OF AN AREA DEGRADED BY GULLY FORMATION IN A RURAL PROPERTY IN THE MUNICIPALITY OF REGENTE FEIJO (SP) - Santana, Alessandro Donaire de [UNESP]; Rodrigues Nunes, Joao Osvaldo [UNESP] (Univ Federal Goias, Dept Geografia, 2021)
Areas degraded by construction of gullies require adoption of conservation practices designed to restore and achieve their recovery. Accordingly, this work aims to present and analyse the results of a partnership between the authors of this study, researchers, government and family farmers to mitigate the impact of an existing gully in a rural property in the northwest of the municipality of Regente Feijo (SP) through conservation practices. Fieldwork was carried out between 2015 and 2017, along with monitoring precipitation between July 2015 and July 2016 and analysis of satellite images from Google Earth between 2015 and 2020. This allowed the gully's expansion to be verified and the results of conservation practices to be assessed implemented in the area. Mechanical intervention, including backfilling the gully and constructing catchment basins and terraces throughout the area, and subsequent adoption of edaphic (soil liming) and vegetative (grass seeding) practices ensured stability of the gully and its surroundings throughout the analysis process. Therefore, despite great changes in the landscape and high costs, mechanical intervention can be adopted in sloping areas in advanced stages of degradation, provided it is associated with edaphic and vegetative practices.
Keywords: Gullies; Conservation practices; Regente Feijo (SP)